Evaluation of comparing urban area land use change with Urban Atlas and CORINE data - Aksoy, Talha; Dabanli, Ahmet; Cetin, Mehmet; Senyel Kurkcuoglu, Muzeyyen Anil; Cengiz, Adem Emre; Cabuk, Saye Nihan; Agacsapan, Balca; Cabuk, Alper (Springer Science and Business Media LLC, 2022)
Urban Atlas (UA) data covering the large urban areas have been produced by the European Environment Agency for a variety of European countries including Turkey since 2006. The use of the UA data for the determination of spatiotemporal land use and density changes in urban areas. UA data of Eskisehir, Turkey, were used in order to detect the spatiotemporal changes between 2012 and 2018. CORINE data-based change detection and NDVI analysis were also made and compared with the results obtained from the UA data. The results based on the UA data revealed that the artificial surfaces in the study area increased by 17.65% and there was a 18.32% increase in the total amount of agricultural lands, natural lands, forests, and vegetation. Although CORINE data-based analyses showed a similar trend in land use/land cover changes, the amount of changes between 2012 and 2018 in CORINE and UA data-based analyses were found to be 4.99% and 17.55%, respectively. A 9.30% mismatch between the UA changes and NDVI difference data was also calculated. Research findings revealed that the utilization of the UA data in the urban territories would be advantageous especially in planning processes to detect and compare the changes in the artificial and non-artificial surfaces and NDVI analysis would be very supportive to control and compare the results. It is also concluded that this study may be a useful model to monitor the cities in accordance with the 2030 and 2050 policies of European Council on Land Use, Land Use Change and Forestry.
Keywords: Databases, Factual; Urbanization; Agriculture; Cities; Forests; Environmental Monitoring; 13. Climate action; 11. Sustainability; 15. Life on land